Enzyme Immobilization on Polypropylene Film: A Role Model for Biocatalytic Polymer Membranes? - Patrizia, Gartner; Jens, Rudat; Maximilian, Bilger; Tom, Grünert; Gisela, Lanza (Journal of Enzymes, 2023)
Polymer electrolyte membrane (PEM) technologies hold promise for sustainable energy solutions, yet pinhole-related challenges persist. Our research introduces a novel biohybrid approach to self-healing, enhancing multiple healing cycles with minimal membrane disruption. Initial steps involve immobilizing enzymes on a polymeric membrane. This study establishes the immobilization process and analytical framework through enzyme immobilization on polypropylene. Applicability and stability are investigated, laying groundwork for potential Nafion™ applications and advancing climate neutral energy. Qualitative analysis employs colorimetric p-NPA assay on polypropylene-immobilized lipase from Candida rugosa (CRL) and Lipase B from Candida antarctica (CALB). Both enzymes hold their temperature optimum at 50°C which is increased by 10°C via immobilization. Diisopropylcarbodiimide (DIC) is optimal for immobilization. Synchronous enzyme and DIC addition is advantageous. After 8 reuse cycles, immobilized enzymes retain 54.3% residual activity. Immobilizates exposed to PEM fuel cell conditions show better stability due to covalent immobilization than free CRL. Yet, declines occur under stressors like 60 °C and concentrated alcohol. Immobilizates remain resilient at pH 3 and under oxidizing as well as reducing conditions constituted by varied gas atmospheres. Considering PEM fuel cells' operational range, in-depth investigations across conditions are vital. Future studies target long-term PEM fuel cell lifespans, focusing on extremophilic enzymes or modifications for high-temperature stability. Subsequently, the transferability of the immobilization method to Nafion™ shall be deliberated based on the outcomes.
Keywords: enzyme immobilization; biocatalytic membrane; polypropylene; Nafion; self-healing; fuel cell; electrolyzers; PEM.